Superior environmental stability of gelatin/CMC complex coacervated microcapsules via chitosan electrostatic modification. (March 2022) - Li, Diewei; Cui, Heping; Hayat, Khizar; Zhang, Xiaoming; Ho, Chi-Tang
Abstract: As an electrostatic deposited coating for gelatin/sodium carboxymethyl cellulose (CMC) coacervates, chitosan was applied to improve their stability and resistance against harsh environment (extreme pH, high ionic strength and high temperature). With eugenol as the core material, gelatin/CMC microcapsules (SM) and gelatin/CMC microcapsules coated by chitosan (DM) were prepared, and their structures were further characterized. To minimize the bridging flocculation of chitosan by the electrostatic interaction, SM were prepared at pH 4.4 and coated by chitosan at pH 5.0. According to the thermal gravimetric analysis results, the degradation temperature of DM was 292 °C compared to 265 °C of SM. The eugenol retention of SM decreased from 65% to 20% as pH increased from 2 to 10, while DM always kept it over 70% between pH 2–10. Moreover, the eugenol retention of DM remained at 70%–80% with an ionic strength of 0–200 mmol/L (pH 4 and 10). CLSM and SEM confirmed that the SM were coated with chitosan, and the Fourier transform infrared (FTIR) spectra showed that electrostatic force played a main role in the binding of gelatin, CMC and chitosan. Circular dichroism (CD) revealed that the secondary structure of gelatin molecules was changed from a flexible pattern to an ordered pattern due to the addition of CMC and chitosan. Consequently, the chitosan coating could improve the stability of complex coacervated microcapsules in harsh environments, which might have a broad prospect to protect essential oils and flavor substances against severe harsh environmental stresses during in the processing of food and pharmaceuticals. Graphical abstract: Image 1 Highlights: ● Chitosan significantly reduced the environmental sensitivity of Gelatin/CMC. ● Dominant force among gelatin, CMC and chitosan was electrostatic interaction. ● Addition of CMC and chitosan made gelatin structure tend to be ordered.